Eastern Europe and the financial sector: where are they going? - SARCINELLI, M. (PSL Quarterly Review, 2013)
The transformation that has taken place already in the countries of central and Eastern Europe and in the former Soviet Union is dramatic. Nevertheless, no single specific reform, taken by itself, is sufficient to ensure the success of the transformation or transition of a major economic sector like that of finance. Banking and financial market reforms, existing and planned, are evaluated for the emergent financial systems. JEL: G18